Behavioral type–environment correlations in the field: a study of three-spined stickleback - Pearish, Simon (2013)
Behavioral type–environment correlations occur when specific behavioral types of individuals are more common in certain environments. Behavioral type–environment correlations can be generated by several different mechanisms that are probably very common such as niche construction and phenotypic plasticity. Moreover, behavioral type–environment correlations have important ecological and evolutionary implications. However, few studies have examined behavioral type–environment correlations in natural populations. In this study, we asked whether some behavioral types of three-spined stickleback were more likely to occur in certain social environments (alone or in a shoal with other stickleback) or in certain microhabitats in a river (in the open or under cover). We found that individuals that were in shoals with other stickleback at the time of collection from the field emerged from a refuge more quickly compared to individuals that were found alone. In addition, fish that were alone in an open microhabitat explored more of a pool compared to fish that were alone in cover, but this difference did not occur among fish that were in shoals at the time of collection. Subsequent analyses of gut contents suggested that differences in microhabitat use were consistent over time. Our study provides some of the first evidence for behavioral type–environment correlations in a natural population of non-human animals.